Nonlinear models for residual generation in fault detection and diagnosis systems applied to the pendubot dynamic system - Levrini, Aldo (2003)
This paper presents a comparison of three nonlinear models used for residual generation. The residual generation is part of a simple fault detection and diagnostics scheme applied to the Pendubot dynamic system operating in closed loop. The compared models are: Hammerstein, neural NARMAX, and Takagi-Sugeno Fuzzy models.